Ecological momentary assessment of daytime symptoms during sleep restriction therapy for insomnia - Miller, C; Kyle, S; Marshall, N; Espie, C (2013)
This study profiles changes in self-reported daytime functioning during sleep restriction therapy (SRT) for insomnia. Ecological momentary assessment (EMA) captured point-in-time symptomatology to map the time-course of symptoms. We hypothesized a deterioration (week 1) followed by improvements at week 3 of therapy relative to baseline. Nine patients with psychophysiological insomnia completed the Daytime Insomnia Symptom Scale (DISS) at rise-time, 12:00 hours, 18:00 hours and bedtime for 1 week before and 3 weeks during SRT. Four validated factors from the DISS were analyzed (alert cognition, positive mood, negative mood and sleepiness/fatigue) across 28 days yielding 17 170 data points. Factors evaluated week (baseline versus weeks 1 and 3) and time of day symptomatology. Insomnia Severity Index scores decreased significantly pre-to-post treatment (mean 18 versus 7). Reflecting acute effects of SRT, significant differences were found for all factors, except negative mood, between baseline and week 1 of SRT, suggesting adverse effects. By week 3, sleepiness/fatigue and negative mood decreased significantly compared to baseline, and positive mood showed a trend towards improvement (P = 0.06). Sleepiness/fatigue displayed a significant week × time of day interaction, explained by a reduction in sleepiness/fatigue at every daytime assessment point (except bedtime, which remained high). A significant interaction for alert cognition was associated with reduction in alertness at bedtime by week 3 and an increase in alertness at rise-time, suggesting that SRT not only improves sleep, but moderates alertness and sleepiness in therapeutic ways. Initial SRT is associated with an increase in sleepiness/fatigue and a decrease in alert cognition. © 2013 European Sleep Research Society.